Climate Smart Agriculture: a primer of local government officials in the Philippines - Gonsalves, Julian Francis; Vidallo, Rene R.; Monville-Oro, Emilita; Dalusag, Joanna B.; Barbon, Wilson John; Jordan J; Rosimo, Magnolia M.; Romero, J.; Servano G; Baguila I; Rosales, B.; Narte J; et al. (2015)
Climate smart agriculture concepts and principles must be simplified for local government officials to be able to operationalize key elements into local development programs. Climate smart agriculture needs to be simplified and often demystified in order to enhance its wider up take at sub regional and local levels.